EFFICIENCY OF PRODUCING FORAGE CROP ALFA ROMA AND CORN (SILOSE) WITH WASTEWATER (European Journal of Interdisciplinary Research and Development, 2024)
Water scarcity situation In order to form a fodder base for livestock in 2022, experimental work on growing crops with river water and wastewater was carried out on the lands of the “Muttaharkhoja” farm in the Bukhara district of the Bukhara region. Based on experience, an experimental system was selected, agrotechnical measures were carried out. According to agrotechnical measures, 16 kg of alfalfa and 20 kg of corn (for silage) were planted per hectare. Additional nutrients for crops grown with river water: Nitrogen – 100 kg/ha, Phosphorus – 150 kg/ha, Potassium – 75 kg/ha for alfalfa crops, mineral fertilizer for corn (silage) with the same amount of Nitrogen – 250 kg/ha, Phosphorus – 175 kg/ha, Potassium – 125 kg/ha, and in the case of tuka, N-735 kg/ha, P-875 kg/ha, K-207.5 kg/ha were given in pure form for alfalfa and corn crops. In both options, the same seasonal irrigation rate for alfalfa crop - 5308 m3/ha, irrigation number 12 times, irrigation system (by harvest) 3-3-2-2-1, for corn (silage) crop - 3585 m3/ha, irrigation number 6 times, irrigation scheme 2-4 amount of water was given. After the phenological observations are made, the result is determined only by the yield. According to the results, the alfalfa crop "Tashkent-3192" irrigated with sewage water had an additional productivity of 7.3 t/ha compared to river water. Compared to the version of "Uzbekistan - 400 BL" variety irrigated with sewage water, 21.8 t/ha less yield was achieved. So, in the case of water scarcity, it is possible to achieve better productivity and economy of river water when growing feed crops for livestock with wastewater.